(untitled) (Journal of Rangpur Medical College, 2025)
Introduction: Temporal bone squamous cell carcinoma (TBSCC) is a rare, aggressive malignancy frequently associated with poor prognosis due to its typically late diagnosis. Objective: This study aimed to analyze diagnostic delays in TBSCC patients, assessing their impact on tumor staging and survival to improve clinical management and healthcare systems. Methods: This retrospective study was conducted at Rajshahi Medical College, Rajshahi, Bangladesh, from June 2020 to July 2021on 150 patients diagnosed with TBSCC. Patients’ records were reviewed for demographic information, clinical history, diagnostic timelines, tumor staging, treatment methods, and survival outcomes. They measured diagnostic delays in three intervals: from symptom onset to the first medical visit, from the first visit to the histological diagnosis, and the overall delay. Survival data were gathered over a 3-year follow-up period. The statistical analysis was conducted on SPSS v26.0, including descriptive statistics, chi-square tests, and Kaplan-Meier survival analysis. Results: Most of the study participants were male (64%) with an average age of 58.3 years. Patients mostly lived in rural areas (61.3%) and had significant smoking histories (54.7%). There were notable diagnostic delays, with 30.7% of patients experiencing total delays of more than six months. Advanced-stage disease (Stage III-IV) was found in 66.7% of the patients. The three-year survival rate was 56.0%. Survival was strongly linked to tumor stage (Stage I: 88.9% vs Stage IV: 25.0%, p=0.007) and diagnostic delay (_3 months: 77.5% vs >6 months: 32.6%, p=0.004). Conclusion: Delays in diagnosis significantly affect survival in TBSCC. Late diagnosis often results in advanced-stage cancer and lower survival rates. Early detection strategies and better access to healthcare are essential for improving outcomes in this aggressive disease. J Rang Med Col. 2025 Sep;10(2): 20-25